The Influence of Treatment with Pegylated Interferon-Alfa and Ribavirin on Neutrophil Function and Death in Patients with HIV/HCV Coinfection - Jablonowska, Elzbieta (Mary Ann Liebert, Inc., 2012)
In patients with human immunodeficiency virus (HIV) as well as in patients with hepatitis C virus (HCV) infection the impairment of neutrophil activity is observed. We decided to analyze how treatment with pegylated interferon-alfa (Peg-IFN-alfa) and ribavirin affects neutrophil function in HIV/HCV coinfected patients. The study group consisted of 18 patients with HIV/HCV coinfection, on combination antiretroviral treatment (cART), aged between 27 and 42 y (mean 33.1±4.5 y). At the beginning of treatment with Peg-IFN-alfa and ribavirin all patients had an undetectable HIV viral load, and CD4 T-cell counts higher than 350 cells/μL. At two time points, before and after 12 wk of treatment with Peg-IFN-alfa and ribavirin, we examined intracellular levels of reactive oxygen species (ROS), and expression of selected adhesion molecules on whole blood neutrophils, along with apoptosis and necrosis of these cells. These analyses were done with flow cytometry. During anti-HCV therapy undetectable HIV levels were maintained in all patients. Treatment with PEG-IFN-alfa and ribavirin resulted in increases in the expression of CD11b and CD18, and decreases of CD16 and CD62L. However, only the change in CD62L expression was statistically significant (p<0.05). Moreover, the treatment resulted in increased apoptosis of neutrophils, while necrosis remained unchanged. After 12 wk of treatment, an increase in ROS production by neutrophils stimulated with PMA was observed (p<0.01). In HIV/HCV coinfected patients on cART, PEG-IFN-alfa and ribavirin treatment caused an activation of neutrophil function, yet it did not affect the suppression of HIV replication.